Pengembangan Sistem Aplikasi SMS Gateway Sebagai Media Penyampaian Data Kehadiaran Siswa Pada Orang Tua - Sri Hartati; Rio Adi Pradana (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2018)
Manual attendance system is still less effective and efficient because there are still many problems in the process because it still uses absentee files that hinder the performance of teachers to know the absenteeism rate of students. Another obstacle faced is the lack of communication and information between the school with the parents of students. This may result in the student being able to lie to the parent that by reporting being in a teaching and learning activity but in fact the student goes to play with his or her friends. This study aims to produce an integrated web-based attendance system with SMS Gateway at SMA Negeri 2 Pringsewu. With SMS Gateway on the system then the system will automatically provide notification to the parents of students about the presence of students at school